Review of EPA's Environmental Monitoring and Assessment Program : overall evaluation ([Distributed by the National Academy Press], 1995)
Reviewing EPA's Environmental Monitoring and Assessment Program (EMAP), this volume retains its belief that EMAP's goals are laudable. Achieving the goals of this ambitious program requires that EMAP successfully meet the difficult scientific, practical, and management challenges. It questions whether and how well all these goals can be achieved.